What else is new about social media influencers? Uncovering their relation and content strategies, and the downsides of being famous - Lou, Chen; Zhou, Xuan (Frontiers in Psychology, 2024)
Prior research on social media influencers (SMIs) often examined questions such as their model of communication with followers, ethical concerns, motivations, and ways of gaining capital. How influencers curate intense and intimate relations and strategize their content creation, and how the influencer industry takes a toll on their physical and psychological wellbeing should be carefully addressed. To fill in this gap, we conducted indepth interviews with 20 SMIs. The findings advance the literature on influencers and influencer advertising by explicating the ways through which influencers maintain intimate and engaged relations with followers, including providing value, creating emotional bond, interacting and co-creating with followers, and disclosing personal life. Second, this research identifies and theorizes four principles -authenticity, topic sensitivity, fact-checking, and strategic sharing of privacy -under which influencers strategize content creations in building human brands. Last, our findings add to the ongoing literature on digital labor by expounding the downsides of influencers being digital labor. This research contributes to the understudied aspect regarding influencers' wellbeing and strategies employed in content creation and relation management in the current influencer literature.